PERBANDINGAN KINERJA KEUANGAN BPRS DAN BPR KONVENSIONAL DI SURABAYA - Nadia Sarasyanti; Atina Shofawati (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
This study aimed to compare the financial performance of The Conventional Rural Bank (BPR) and Islamic Rural Bank (BPRS) in Surabaya. The Sample is acquired using saturate method. The writer selects all Islamic Rural Bank (BPRS) and Conventional Rural Bank (BPR) in Surabaya with in the year of 2014 – 2016. Methods of data analysing using independent Samples T – Test and Mann Whitney Experiment. The results of this research shows that there i significant differences upon NPF or NPL ratio, FDR or LDR ratio, ROA, NIM or NOM, and CAR. Generally, on the aspec of Risk Profile, Earning, and Capital point of view, financial performances of the Conventional Rural Bank (BPR) showed that financial performances isbetter than the Islamic Rural Bank (BPRS). REFERENCESAntonio, Muhammad Syafi'i. (2001). Bank Syariah dan Teori ke Praktik. Jakarta: Tazkia Cendikia.Arifin, Zainul. (2005). Dasar - dasar Manajemen Bank Syariah . Yogyakarta: Pustaka Alvabet.Dendawijaya, Lukman. 2006. Manajemen Perbankan. Yogyakarta: Ghalia IndonesiaIhsan, Dwi Nur'aini. 2013.Analisis Laporan Keuangan Perbankan Syariah, Banten: UIN Jakarta Press.Iswandari, Mona. (2011). KINERJA KEUANGAN BANK PERKREDITAN RAKYAT DAN BANK PEMBIAYAAN RAKYAT SYARIAH: STUDI KASUS di Yogyakarta. 31-45.Johnso, Frank P, dan Johnson Richard D.1985. Commercial Bank Management . New York: The Dryden Press. h. 331 - 332.Laksamana. (2009). Account Officer Bank Syariah memahami praktik proses Pembiayaan di Bank Syariah. Jakarta: PT Gramedia.Muhammad. (2002). Manajemen Dana Bank Syariah. Yogyakarta: Ekonomisia.Ningtyas, Puspita. 2013.Perbandingan Kinerja Keuangan Bank Konvensional dan Bank Syariah Berdasarkan Analisis Rasio Keuangan. Jurnal. Universitas Brawijaya.Rizki Yudi Prasetyo 2012 “Pengaruh Risiko   Usaha Terhadap Capital Adequacy Ratio (CAR) pada Bank Umum Swasta Nasional Go Public”. Skripsi Sarjana tak diterbitkan. STIE Perbanas Surabaya.Quth, Syahid Sayyid. (2001). Tafsir Fi Zhilalil - Quean di Bawah Naungan Al - Quran Jilid 1. Jakarta: Gema Insani Press.Rani, L.N. 2013. Analisis Faktor - Faktor yang Mempengaruhi Non Performing Financing (NPF) Pada Perbankan Syariah di Indonesia. Tesis tidak diterbitkan. Universitas Airlangga Surabaya.Sukmana, Raditya. (2016). Islamic Banks vs Conventional Banks . An Analysis on Financial Performances, 81 - 90.Sulistianingrum, Dwi. R. (2013). Analisis Pengaruh Financing to Deposit Ratio (FDR), Dana Pihak Ketiga (DPK), Sertifikat Bank Indonesia Syariah(SBIS), dan Non Performing FInancing (NPF) Terhadap Return on Asset (ROA), Periode Januari 2009 - Desember 2012. Jakarta: Universitas Islam Negeri Syarif Hidayatullah.Sumitro, Warkum. (2002). Asas - Asas Perbankan Islam dan Lembaga Terkait (BMI dan Takaful di Indonesia). Jakarta: PT Raja Grafindo Persada, Indonesia.Windriya, Anafil. (2014). Analisis Pengaruh Faktor Eksternal dan Faktor Internal Bank Terhadap Profitabilitas Bank Umum Syariah di Indonesia (Periode 2008-2013). Semarang: Universitas Diponegoro.www.bi.go.id